Foreign currency housing loans and exchange rates – risk evaluation - Buszko, Michał (Copernican Journal of Finance & Accounting, 2013)
The aim of this paper is an evaluation of foreign exchange housing loans granted in Poland. In the paper, there was conducted research of portfolio of housing loans, its structure and changes, especially with consideration to the currency of debts. Also, a foreign currency loans profitability accordingly to the time of obtaining the loan by the debtor was analyzed. The author statistically analyzed volatility of foreign exchange rates of major currencies traded in Poland. The results were compared versus swiss franc and euro. The research indicated very high level of swiss franc volatility and risk as well as confirmed high level of risk of financing in swiss currency over euro.